Construction of a pillar[6]arene based water-soluble supramolecular pseudopolyrotaxane driven by cucurbit[8]uril-enhanced π–π interaction. Issue 84 (6th October 2016) - Yang, Jie; Shao, Li; Yuan, Jiayin; Huang, Feihe
Abstract : A water-soluble pillar[6]arene-based linear supramolecular pseudopolyrotaxane with controlled compositions and structures connected through cucurbit[8]uril host-enhanced π–π interaction was successfully fabricated. Abstract : A new pillar[6]arene based water-soluble supramolecular pseudopolyrotaxane whose repeating units are connected through cucurbit[8]uril-enhanced π–π interaction is successfully fabricated.